STUDI PENANGANAN BENCANA GEMPA DI BANTUL 27 MEI 2006 - Didirianti, Desneri; Kironoto, Bambang Agus; Nurrochmad, Fatchan (Civil Engineering Forum Teknik Sipil, 2007)
On May 27 th , 2006 at 05:53, 57, a 5,9 Richter scale earthquake occurred. Bantul Regency in Yogyakarta Province was the most severe area. However, existing institutions had limited capability to perform a proper disaster management they also failed to generate the community to participate, especially during the emergency respose period. Therefore, it is required to have an integrated policy for disaster management to meet related parties expectations and to conduct more optimum disaster management. The objective of this study is to obtain best alternatives in handling disaster using the Decission Support System (DSS) eith Analytical Hierarchy Process (AHP) as the method. Three alternatives were analized formatting special office for disaster management (Alternative 1), formatting community based disaster management (Alternative 2), and ascociating the disaster management between interrelated agencies and the local government as the control center (Alternative 3). These alternative were selected based on fuor criterias management, financial, capacity and policy aspect. This study was taken during, the emergency response period performed by SATLAK PBP Bantul. Input for the analysis was questionnaire result given to 120 respondents composing af 30 respondents from bureaucratic element (SATLAK and SATKORLAK PBP members) and 90 respondents from nine villages in three districts. Numeric values were given to each element of the questionnaire result (criterion, sub criterion and alternative). Then, the values were compared to the established comparison scale obtain the lever of interest. Result of this study showed that each criterion of financial, management policy and capacity aspects weighted 0,273, 0,265, and 0,208 respectively. The best alternative of optimum disaster management was alternative 2. The second anf the third were alternative 1 and alternative 3. The community based organizations objective was to improve the people participation in pertaining, preventive, counter measuring and self healing by actively involve in the planning and executing process of disaster management.